Spatial and temporal variability in hydrochemistry of a small-scale dolomite karst environment - Sheikhy Narany, Tahoora; Bittner, Daniel; Disse, Markus; Chiogna, Gabriele (Environmental Earth Sciences, 2019)
Dolomite karst systems are less common and less exploited than limestone systems, but still they can significantly contribute to drinking water supply in many countries. The knowledge about spatial and temporal variations of hydrochemical parameters of such systems is much more limited than for limestone karst aquifers. In the present research, 40-year-long observations of hydrochemical parameters gathered from five springs and a pumping well in Waidhofen an der Ybbs (Austria) were used to show the variability of chemical water composition in a small-scale ( 10 km2) dolomite karst system. Integration of classic geochemical methods and multivariate statistical analysis revealed that the hydrofacies correlate directly with the lithofacies (dolomite) in the study area. At the same time, measured concentrations of Ca2+, Mg2+, Na+, Cl−, and HCO3− allow for a classification of the springs in three groups based on their ionic ratios. This classification highlights the spatial and temporal variability that can be encountered in dolomite karst systems, even on small spatial scales, that are relevant for water suppliers. Moreover, temporal observations of hydrochemical parameters show increasing trends of nitrate concentrations in all sampling points, though with different rates. The analysis of the stable isotopes δ15N–NO3 and δ18O–NO3 revealed that nitrification processes in forest floors and mineral soils are the main source of nitrate in most locations investigated. The findings of the present study highlight the necessity of a detailed temporal and spatial distributed monitoring to support water resources management in dolomitic karst aquifers.
CRIS-Team Scopus Importer:2024-04-17
Keywords: Austria; Dolomite karst systems; Drinking water; Hydrochemistry; Small-scale